Surgical resection of a bilateral temporomandibular joint ankylosis and interposition gap arthroplasty using bilateral temporo-parietal fascial flap in a 5 years old child: treatment challenges and literature review - Jangra, Mahesh; Chapa, Uday K.; Kumari, Kamlesh; Gupta, Tarush (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Temporomandibular joint (TMJ) ankylosis is a debilitating state that involves fusion of glenoid fossa and condyle of mandible. This can lead to restriction in mouth opening and mandibular movements. Subsequently, patient develops difficulty in chewing, speech, breathing as well as poor dental hygiene. All of these have detrimental effects on patient’s wellbeing and their quality of life. TMJ ankylosis can also have secondary effects on facial growth like asymmetry of face, retro or micrognathia, malocclusion, anterior or posterior open bite and overcrowding of teeth specially if it presents at early age. Main event that leads to TMJ ankylosis is trauma but this can occur as a secondary insult to surgery, local and systemic infections or diseases like chronic otitis media, tuberculosis, juvenile rheumatoid arthritis and septic arthritis. The management of TMJ ankylosis poses a significant challenge because of technical difficulties and a high incidence of recurrence. It is mainly managed by surgery with different options like gap and interpositional arthroplasty, reconstruction arthroplasty or distraction osteogenesis and aggressive post op physiotherapy. Here, we present a case five years old girl child with post traumatic TMJ ankylosis who was managed with excision of ankylotic mass and interpositional arthroplasty by using bilateral temporo-parietal fascial flap. She was followed for a 1 year and had adequate mouth opening and no recurrence.